Occupational risk factors for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection among healthcare personnel: A 6-month prospective analysis of the COVID-19 Prevention in Emory Healthcare Personnel (COPE) Study. (14th November 2022) - Howard-Anderson, Jessica R.; Adams, Carly; Dube, William C.; Smith, Teresa C.; Sherman, Amy C.; Edupuganti, Neena; Mendez, Minerva; Chea, Nora; Magill, Shelley S.; Espinoza, Daniel O.; Zhu, Yerun; Phadke, Varun K.; et al.
Abstract: Objectives: To determine the incidence of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection among healthcare personnel (HCP) and to assess occupational risks for SARS-CoV-2 infection. Design: Prospective cohort of healthcare personnel (HCP) followed for 6 months from May through December 2020. Setting: Large academic healthcare system including 4 hospitals and affiliated clinics in Atlanta, Georgia. Participants: HCP, including those with and without direct patient-care activities, working during the coronavirus disease 2019 (COVID-19) pandemic. Methods: Incident SARS-CoV-2 infections were determined through serologic testing for SARS-CoV-2 IgG at enrollment, at 3 months, and at 6 months. HCP completed monthly surveys regarding occupational activities. Multivariable logistic regression was used to identify occupational factors that increased the risk of SARS-CoV-2 infection. Results: Of the 304 evaluable HCP that were seronegative at enrollment, 26 (9%) seroconverted for SARS-CoV-2 IgG by 6 months. Overall, 219 participants (73%) self-identified as White race, 119 (40%) were nurses, and 121 (40%) worked on inpatient medical-surgical floors. In a multivariable analysis, HCP who identified as Black race were more likely to seroconvert than HCP who identified as White (odds ratio, 4.5; 95% confidence interval, 1.3–14.2). Increased risk for SARS-CoV-2 infection was not identified for any occupational activity, including spending >50% of a typical shift at a patient's bedside, working in a COVID-19 unit, or performing or being present for aerosol-generating procedures (AGPs). Conclusions: In our study cohort of HCP working in an academic healthcare system, <10% had evidence of SARS-CoV-2 infection over 6 months. No specific occupational activities were identified as increasing risk for SARS-CoV-2 infection.